1970
DOI: 10.1002/ps.2780010304
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide residues in foodstuffs in Great Britain: XIII.—Organochlorine residues in cereals, pulses and nuts

Abstract: Results are presented for the determination of organochlorine insecticide residues in grain, pulses and nuts sampled on arrival in Britain during the 2+ years up to June 1969. BHC was detected in nearly every sample but the general level was low, most samples containing less than 0.1 ppm. DDT was found less frequently. Very few samples contained more than 1 pprn of either insecticide. DDE in trace amounts was found in about 10% of the samples of grain and nuts and TDE was found in one sample of grain. The only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1973
1973
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Pesticide residues have been detected in milk frequently in various researches. A study conducted by the USDA Pesticide data programme showed that 96% of the samples contained dicchloro-diflouro ethane (DDE), 99% DPA, 41% dieldrin, 25% synthetic pyrethroids and 9% had 3 hydroxyfurans which is a breakdown product of carbamate insecticides (Thompson and Fishwick, 1970). Sassine et al (2004) studied cypermethrin contamination Iftikhar et al 483 in dairy milk samples of Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Pesticide residues have been detected in milk frequently in various researches. A study conducted by the USDA Pesticide data programme showed that 96% of the samples contained dicchloro-diflouro ethane (DDE), 99% DPA, 41% dieldrin, 25% synthetic pyrethroids and 9% had 3 hydroxyfurans which is a breakdown product of carbamate insecticides (Thompson and Fishwick, 1970). Sassine et al (2004) studied cypermethrin contamination Iftikhar et al 483 in dairy milk samples of Brazil.…”
Section: Discussionmentioning
confidence: 99%